Leizarragarengan -ra eta -raten erabilerari buruz - Igartua, Mirari (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1986)
This is an analysis of the use of -ra and -rat in the work of Leizarraga. Verbs such as ethorri "to come", joan "to go", egotzi "to send", itzuli "to return", behatu "to look at", altxatu "to rise" and goitutu "to rise" are studied, the conclusion being that the choice between these alative suffixes does not depend on the verb itself but on the space-relation it sets.